What are mixed methods prevalence rate studies analysing? - Cameron, Roslyn (ECRM, 2014)
Mixed methods research has claimed to be the third methodological movement and is growing in popularity and usage across many disciplines and fields of inquiry. Mixed methods prevalence rate studies are becoming increasingly applied to assist the mixed methods research community analyse the utility of mixed methods (mm) across specific disciplines and academic fields. Mixed methods prevalence rate studies refer to a type of investigation which analyses the proportion of published articles that use particular methodological approaches. according to Alise and Teddlie (2012, p. 104) 'researchers examining prevalence rates are interested in determining the percentage of QUAN, QUAL, and mixed methods research (MMR) studies that occur within different disciplines across the social sciences. these rates are especially important to individuals interested in MM, because they indicate the degree of awareness that researchers in different disciplines have of the utility of MM research and how it can be used to uniquely answer certain types of questions in their areas of study.' The purpose of this paper is to examine the growing array of mixed methods prevalence studies in the fields of business and management. This study is exploratory and has employed a qualitative content analysis approach to analyse mixed methods prevalence studies. The sample for this content analysis is the 15 mixed methods prevalence rate studies across business and management disciplines. It is anticipated that this study will yield more insight into what the current issues are in publishing mixed methods studies and how mixed methods studies are being judged in terms of their design, rigour, quality and reporting.